Understanding Aristotle's Notion of the Mean: A Case Study in Anger - Stewart, Heather (Labyrinth, 2019)
In this paper, I argue that purely quantitative understandings of Aristotle's concept of "the mean" (as presented in Nicomachean Ethics) are oversimplified, and I make this argument by analyzing the particular emotion of anger. Anger, I contend, helps to complicate the purely quantitative understanding of the mean, insofar as, I argue, the amount of anger experienced is not the morally salient feature in determining whether or not the anger is virtuous. Rather, anger is one example of an emotion or trait for which other, non-quantitative parameters of the mean are more salient, giving us a more nuanced understanding of what the mean is. Anger is virtuous not when it is in the right measurable degree, but rather when it is directed at the proper target. In this way, the virtue-making property of anger is distinctly qualitative. Examining anger provides insight into the concept of the mean and its role in Aristotle's ethics, and also helps to shed light on contemporary debates about political anger.